2020
DOI: 10.1016/j.worlddev.2020.105067
|View full text |Cite
|
Sign up to set email alerts
|

How health inequality affect responses to the COVID-19 pandemic in Sub-Saharan Africa

Abstract: The COVID-19 outbreak has infected millions of people across the world, caused hundreds of thousands of deaths, and collapsed national economies. Recognizing the importance of handwashing in preventing the spread of COVID-19, concerns have arisen about the condition of millions of Africans who lack access to hygiene facilities and clean water services. This paper compiles evidence from the WHO-UNICEF data to show the health disparities that limit the capacity of African countries to effectively address the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 23 publications
2
36
0
1
Order By: Relevance
“…The same concerns are raised by Wang and Tang [ 29 ] who note that in the case of China, health equity should be the focus of all policies designed to strengthen the country’s health system and emergency responses during health crises in the future. Okoi and Bwawa [ 30 ] similarly highlight the difficulties faced by Sub-Saharan African countries in dealing with the COVID-19 outbreak in the absence of basic hygiene facilities. Future studies might examine why some democracies have managed to put in place more targeted policies over others, and identify the precise policies and processes that have affected the disparities in the death rates.…”
Section: Resultsmentioning
confidence: 99%
“…The same concerns are raised by Wang and Tang [ 29 ] who note that in the case of China, health equity should be the focus of all policies designed to strengthen the country’s health system and emergency responses during health crises in the future. Okoi and Bwawa [ 30 ] similarly highlight the difficulties faced by Sub-Saharan African countries in dealing with the COVID-19 outbreak in the absence of basic hygiene facilities. Future studies might examine why some democracies have managed to put in place more targeted policies over others, and identify the precise policies and processes that have affected the disparities in the death rates.…”
Section: Resultsmentioning
confidence: 99%
“…Burström and Tao ( 2020 ) similarly remarked that COVID-19 had a more significant impact on people in the lower socio-economic class and minority groups. With reference to Africa, Okoi and Bwawa ( 2020 ) also showed that health inequalities adversely affected people’s responses to COVID-19.…”
Section: Reflection 2: Health Inequalities and Health Disparitiesmentioning
confidence: 99%
“…The issue of the COVID-19 outbreak and its impacts have been the focus of extensive research among many scholars. One strand of studies examines the impact of COVID-19 on different industries, such as Mishra and Rampal [18] , Okoi and Bwawa [21] for medical industry, Fezzi and Fanghella [9] for electricity industry, Sigala [25] and Lee and Chen [12] for tourism industry, Wang et al. [28] for insurance industry, and Liu et al.…”
Section: Introductionmentioning
confidence: 99%